PENGEMBANGAN LKPD IPS BERBASIS SCIENTIFIC APPROACH UNTUK MENINGKATKAN BERPIKIR KREATIF (STUDI KASUS SDN PUNGGULREJO DAN SDN SOKO 1 TUBAN JAWA TIMUR) - Hidayah, Mazroatul (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Abstract This research aims to develop IPS (Social Sciences) LKPD (Student worksheet) based on a scientific approach in order to improve student learning outcomes and creative thinking skills. Data were obtained from class VI SDN 1 Soko and class VI SDN Tunggulrejo, Rengel District, Tuban Regency, East Java. This research method uses research and development methods. This method is carried out in the 4-D cycle of Thiagarajan and Semmel (1974), namely Define, Design, Develop, and Deseminate. The results of this research-development are 1.) LKPD developed is declared very feasible by the validator both in terms of material with 87.5% and media with 88.2%. 2.) The level of effectiveness of the LKPD developed based on the results of the percentage of completeness of the experimental class of 93.1% was declared very effective. Meanwhile, the effectiveness level with the N-gain value is 71.35%. Thus, the LKPD IPS based on a scientific approach with the theme of economic activity in the surrounding environment is declared effective in increasing students’ creativity and cognitive. Keyword: LKPD Development, Social Sciences, Economic Activities, Creative Thinking